Determinants of the overall quality of life of older persons who have difficulty seeing: The importance of the ability to get around - la Grow, S.; Yeung, Polly; Towers, A.; Alpass, F.; Stephens, C. (American Foundation for the Blind, 2011)
A model of vision rehabilitation that assumes that functional ability will affect the emotional and psychosocial adjustment of older persons with visual impairments, and ultimately their quality of life, was assessed using structured equation modeling. The proposed model was upheld. In addition, the ability to get around was found to contribute to both functional ability and quality of life.